ERGONOMIC SEWING WORKSTATION DESIGN FOR BETTER PRODUCTION PROCESSES IN THE BAG INDUSTRY - Mochammad Charis Hidayahtullah; Galuh Puspita Sari (Politek ATK Yogyakarta Press, 2024)
Yogyakarta is one of the province's industrial centers producing bags which are quite well-known in Indonesia. As one of the provinces with a rapidly growing creative industry in Indonesia, the industry sample taken in this study is a bag production house called Difa Bag in Bantul Yogyakarta, which produces bags made of leather, canvas, and polyester materials. This research aims to observe and analyze field conditions in bag production and produce a workstation design that is ergonomy for workers in the sewing processes. Research using qualitative methods in the form of field observations obtained data that the height in the sitting position, hand reach, knee height in the sitting position, and natural sitting height obtained data that is not by proper ergonomic standards. The absence of a backrest in a sitting position also results in a hunched back for a longer time. Sewing work activities that lack ergonomics and are carried out repeatedly affect the performance of workers so that they tire quicker which causes a less-than-optimal quality and quantity of bag production. This more ergonomic sewing workstation design concept can provide comfort, safety and increase worker productivity in the bag industry in Indonesia.